2023
DOI: 10.1186/s12966-023-01442-0
|View full text |Cite
|
Sign up to set email alerts
|

Play Active physical activity policy intervention and implementation support in early childhood education and care: results from a pragmatic cluster randomised trial

Abstract: Background Policy interventions to increase physical activity in early childhood education and care (ECEC) services are effective in increasing physical activity among young children. However, a large proportion of ECEC services do not have nor implement a physical activity policy. Play Active is an evidence-informed physical activity policy intervention with implementation support strategies to enable ECEC services to successfully implement their policy. This study examined the effectiveness, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 32 publications
0
2
0
Order By: Relevance
“…Moreso, suggested that respective authorities must design their programs within the physical literacy principle. This was backed up by the study findings that getting support by including the program within the scope of plans and policy was an advantage (Adams et al, 2023).…”
Section: Theme 2: Physical Literacy Focusmentioning
confidence: 98%
“…Moreso, suggested that respective authorities must design their programs within the physical literacy principle. This was backed up by the study findings that getting support by including the program within the scope of plans and policy was an advantage (Adams et al, 2023).…”
Section: Theme 2: Physical Literacy Focusmentioning
confidence: 98%
“…It is evident that early childhood education plays a crucial role in the development of children's social, cognitive and emotional skills (Adams, et al, 2023). Play-based learning emphasizes the pedagogical benefits of play, providing learners with the exploring opportunities of their surroundings, developing social interactions, and critical thinking.…”
Section: Introductionmentioning
confidence: 99%